IMPACT OF STUDENT LOAN IN EMPOWERMENT THE COMMUNITIES - Bella Ghia Dimmera (Management and Sustainable Development Journal, 2019)
This study aims to collect and analyze articles related to the impacts of student loan in realizing community empowerment. The background of this study is higher education costs cannot be afforded by the majority community. Although many government have launched student loan programs, the debate over failure of student loan programs in developing countries has not been resolved. The method used in this study is a literature review by collecting various sources of articles related to the issues discussed. Based on the articles collected, there are many problems such as irrelevant student loan policies, challenges in their application system, loans that could not be repaid that eventually burdened the community. The role of the government, the trust of banks, and the commitment of the community are factors that determine the success rate of achieving this student loan.